Analysis of the Potential of the Panatapan Panyabungan Natural Tourism Area, Mandailing Natal Regency - Aulia Ryza Aqilla; Nurhasan Syah; Iswandi Umar; Heldi (Jurnal Penelitian Pendidikan IPA, 2025)
Nature tourism in Mandailing Natal Regency, North Sumatra has promising potential. Statistical data shows an increase in local tourist visits of 6,274 people in the 2023-2024 period. This increase has a positive impact on community and government income, but has the potential to have a negative impact on ecological aspects if it exceeds the carrying capacity of the area. Therefore, the strategy for developing the area is an important factor in realizing sustainable tourism activities. This study was conducted in September-October 2024 with the aim of analyzing the strategy for developing sustainable tourism areas. Data collection was carried out to identify the carrying capacity of each tourist attraction using a SWOT (Strength-Weakness-Opportunities-Threats) analysis through interviews with relevant stakeholders. The results of the carrying capacity analysis show that this area is still able to accommodate tourist activities. The main strategy for sustainable development recommended is optimizing the area by expanding areas that have the potential for beautiful scenery as the main attraction, as well as improving supporting facilities and infrastructure in the future.